Numerical study of the installation configuration of four Savonius hydrokinetic turbines in the cooling water channel of PAITON Power Plant - Wulaningtyas, Oktafika; Yuwono, Tri Yogi (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
The energy crisis caused by decreasing fossil fuel reserves encourages the development of renewable energy, one of which is water energy from rivers, lakes, and canals. The Paiton PLTU cooling water channel, which is 2 km long, 15 m wide, and 10 m deep with a flow speed of 1-2.8 m/s, has great potential as an energy generator by installing a Savonius hydrokinetic turbine. This study aims to identify the optimal tandem spacing to avoid turbine interaction. This study uses numerical simulations using Ansys Fluent 2023 R2 with four tandem turbines rotating Counterclockwise and Clockwise. The distances between the turbines (T/D) studied are 2.1, 4.4, 60, and 300. At close T/D distances (2.1 and 4.4), the turbines influence each other, reducing the performance of the front turbine. When the distance increases to T/D = 60, the rear turbine influence decreases, so the front turbine can perform similarly to a single turbine. At T/D = 300, both turbines operate optimally with minimal interaction, achieving efficient performance and increased torque and power output.